British Women Education Officers and progressive education for an independent Nigeria. (3rd September 2018) - Whitehead, Kay
ABSTRACT: This article focuses on the work of three British Women Education Officers (WEOs) in Nigeria as the colony was preparing for independence. Well-qualified and progressive women teachers, Kathleen Player, Evelyn Clark (née Hyde), and Mary Hargrave (née Robinson), were appointed as WEOs in 1945, 1949, and 1950 respectively. I argue that the three WEOs endeavoured to reconcile their British cultural values, progressive education, English language instruction, and the intricacies of Nigerian cultures in order to prepare students for life and work in an independent Nigeria. Their roles were diverse, encompassing administration and teaching, teacher education, and leadership of girls' boarding schools and residential training colleges where English was the language of instruction. Following an outline of the WEOs' prior experiences, I compare and contrast their approaches to progressive education, beginning with Clark's endeavours to make girls' education "a graft that would grow onto and into their own way of life" at the Women's Training College, Sokoto, in far Northern Nigeria. Then I discuss Robinson's work in a men's elementary training college at Bauchi where she dispensed a "down-to-earthpractical " progressive education to prospective primary school teachers. Finally, Player gave girls "as complete an education as possible for life as a worker, wife and mother" at Queen Elizabeth School, the first government secondary school for girls in Northern Nigeria. Each situation illustrates the complex social relations involved in realising WEOs' commitments to progressive education as an emancipatory project.